An age-associated decrease in the frequency of C4B*Q0 indicates that null alleles of complement may affect health or survival - Arason, Gudmundur Johann; Bodvarsson, Sigurdur; Sigurdarson, Sigurdur Thor; Sigurdsson, Gardar; Thorgeirsson, Gudmundur; Gudmundsson, Sveinn; Kramer, Judit; Füst, Georg (Annals of the New York Academy of Sciences, 2007)
To access publisher full text version of this article. Please click on the hyperlink in Additional Links field We studied the distribution of complement C4, C3, and factor B allotypes in 423 healthy Icelandic subjects from 17 to 89 years of age. A marked decrease was observed in the carrier frequency of variant alleles of complement C4B (C4B(*)Q0) and C3 (C3(*)F). These results confirm our previous observations on Hungarian subjects and suggest a negative effect of C4B(*)Q0 on health or survival.